2018
DOI: 10.1016/j.neo.2018.08.004
|View full text |Cite
|
Sign up to set email alerts
|

FOXF1 Induces Epithelial-Mesenchymal Transition in Colorectal Cancer Metastasis by Transcriptionally Activating SNAI1

Abstract: Forkhead Box F1 (FOXF1) has been recently implicated in cancer progression and metastasis of lung cancer and breast cancer. However, the biological functions and underlying mechanisms of FOXF1 in the regulation of the progression of colorectal cancer (CRC) are largely unknown. We showed that FOXF1 was up-regulated in 93 paraffin-embedded archived human CRC tissue, and both high expression and nuclear location of FOXF1 were significantly associated with the aggressive characteristics and poorer survival of CRC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 52 publications
0
22
0
Order By: Relevance
“…New EMT marker genes that are labeled by H3K4Ac and regulated by HDAC3 are identified, including FOXF1 , SIRT2 , GLI1 , SMO , BMI1 , and so forth. FOXF1 has been recently implicated in cancer progression and metastasis of breast cancer, lung cancer, and colorectal cancer, by inducing EMT through upregulating lysyl oxidase and suppressing Smad2/3 signaling, or through transcriptionally activating SNAI1 . The role of SIRT2 in regulating the Akt/GSK‐3β/β‐catenin pathway to mediate EMT and predict prognosis in hepatocellular carcinoma and esophageal squamous cell carcinoma has also been reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…New EMT marker genes that are labeled by H3K4Ac and regulated by HDAC3 are identified, including FOXF1 , SIRT2 , GLI1 , SMO , BMI1 , and so forth. FOXF1 has been recently implicated in cancer progression and metastasis of breast cancer, lung cancer, and colorectal cancer, by inducing EMT through upregulating lysyl oxidase and suppressing Smad2/3 signaling, or through transcriptionally activating SNAI1 . The role of SIRT2 in regulating the Akt/GSK‐3β/β‐catenin pathway to mediate EMT and predict prognosis in hepatocellular carcinoma and esophageal squamous cell carcinoma has also been reported.…”
Section: Discussionmentioning
confidence: 99%
“…GLI1 and SMO expression in HNSCC patients and their relation to clinicopathological factors Estimated by χ 2 or Fisher's exact test (if expected count was less than 5). or through transcriptionally activating SNAI1 40. The role of SIRT2 in regulating the Akt/GSK-3β/β-catenin pathway to mediate EMT and predict prognosis in hepatocellular carcinoma41 and esophageal squamous cell carcinoma42 has also been reported.…”
mentioning
confidence: 99%
“…Western blot was performed according to standard methods as described previously [34]. Anti-Siah1 (Abcam, #ab69638, dilutions: 1:200), anti-phospho-AKT (Cell Signaling Technology, #C31E5E, dilutions: 1:200), anti-AKT (Cell Signaling Technology, #11E7, dilutions: 1:1000), anti-JNK (Bioworld Technology Inc., #BS1544, dilutions: 1:200), anti-phospho-JNK (Bioworld Technology Inc., #BS4322, dilutions: 1:1000), and anti-YAP (Cell Signaling Technology, #8418, dilutions: 1:200) antibodies were used for Western blot.…”
Section: Rt-qpcr and Western Blot Analysesmentioning
confidence: 99%
“…Additionally, SNAI1 has been reported to directly or indirectly inhibit the activity of p53, one of the most important anti-oncogene during carcinogenesis [14]. Previous studies have reported that high expression of SNAI1 was signi cantly correlated with tumor metastasis, recurrence and worse prognosis in multiple types of malignancies, including CRC [15], lung cancer [16], breast cancer [17], and ovarian cancer [18]. However, the role of SNAI1 in the carcinogenesis and metastasis of CRC cells remains largely unclear and deserves more attention.…”
Section: Introductionmentioning
confidence: 99%